2012
DOI: 10.1038/eye.2012.160
|View full text |Cite
|
Sign up to set email alerts
|

Parental smoking and childhood refractive error: the STARS study

Abstract: Purpose To assess the relationship between parental smoking and childhood refractive errors in Singapore Chinese children aged 6-72 months recruited through the STrabismus, Amblyopia, and Refractive errors in Singaporean children study. Methods A total of 4164 children were recruited, with a positive response rate of 72.3% (n ¼ 3009). Cycloplegic refraction measurements were obtained from all children by trained eye professionals. Parents underwent an interviewer-administered questionnaire with information on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 17 publications
3
44
0
Order By: Relevance
“…Because nicotine activates nAChRs and is a constituent of tobacco smoke, the anti‐myopia effect of nicotinic AChR antagonists has stimulated the investigation of whether tobacco smoke exposure might affect refractive development in children . Several cross‐sectional clinical reports have found that passive tobacco smoke exposure associates with a shift in refractive distribution towards hyperopia, i.e., lower myopia prevalence, in exposed children . In contrast, a long‐term prospective study performed in British adults by Rahi et al, found that myopia was positively associated with maternal smoking in the first trimester; this is the only population‐based study whose direction of effect conforms with the anti‐myopia action in chicks of antagonists to nAChRs .…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Because nicotine activates nAChRs and is a constituent of tobacco smoke, the anti‐myopia effect of nicotinic AChR antagonists has stimulated the investigation of whether tobacco smoke exposure might affect refractive development in children . Several cross‐sectional clinical reports have found that passive tobacco smoke exposure associates with a shift in refractive distribution towards hyperopia, i.e., lower myopia prevalence, in exposed children . In contrast, a long‐term prospective study performed in British adults by Rahi et al, found that myopia was positively associated with maternal smoking in the first trimester; this is the only population‐based study whose direction of effect conforms with the anti‐myopia action in chicks of antagonists to nAChRs .…”
Section: Introductionmentioning
confidence: 77%
“…Because of its prominent biological actions, nicotine is presumed to be responsible for this finding, even though tobacco smoke contains many additional active chemicals. Besides variability between studies, the effect estimates may have been confounded by socioeconomic status . Socioeconomic status such as educational level is a risk factor for refractive error .…”
Section: Introductionmentioning
confidence: 99%
“…(11,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) No attempt was made to adjust the results for important variables, such as gender or ethnicity, or to weigh the results according to differences in methods. Statistical analysis was performed using the IBM SPSS Statistics version 19.0 (IBM Corp, Armonk, NY, USA).…”
Section: Abstract: Diabetes Hba1c Hyperglycaemia Myopia Refractionmentioning
confidence: 99%
“…The prevalence rates were taken directly from cohort-, army-and population-based studies in Singapore published from 2001 onwards. (11,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) To calculate the average rate of prevalence, results were weighted according to the number of subjects participating in the study. The weighted average (x) was calculated using the following formula:…”
Section: Abstract: Diabetes Hba1c Hyperglycaemia Myopia Refractionmentioning
confidence: 99%
See 1 more Smart Citation